Thyroid nodule rupture and hyperthyroidism following radiofrequency ablation: A case report - Le Thi My, MD; Tran Thi Hoang Anh, MD; Nguyen Thi Thanh Hien, MD; Vu Mai Quynh, MD; Ngo Thi Thanh Tu, MD; Pham Vu Hiep, MD; Ngo Van Doan, PhD; Duong Manh Cuong, MD; Thieu Thi Tra My, MD (Radiology Case Reports, 2025)
Radiofrequency ablation (RFA) plays a crucial role in the treatment of benign thyroid nodules by offering a minimally invasive alternative to surgical interventions. Nodule rupture is an uncommon complication of RFA. We present a case of nodule rupture and hyperthyroidism after RFA 41 days in a 45-year-old male patient. The neck ultrasound revealed the disruption of the thyroid nodule capsule and a mass adjacent to the thyroid nodule. Thyroid function tests suggested of hyperthyroidism. The patient was received conservative treatment. Follow-up, the biochemical tests showed TSH and FT4 returned to normal limits 2 weeks later. Five months after radiofrequency ablation shows the thyroid nodule was decrease 92% volume compared to the volume immediately postablation and the soft tissue lesion in the right neck region was completely regressed.